(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Unsafe street food will directly affect the health of consumers, causing serious consequences such as acute and chronic food poisoning, food-borne diseases and can cause serious health problems. environmental pollution, affecting tourism and economic development of the country [2]. Objective: Describe situation of food safety knowledge of processors on street food businesses at Thot Not District, Can Tho city in 2022. Methods: Cross-sectional survey, quantitative study. Select all processors at 270 street food businesses in Thot Not District, Can Tho City from January 2022 to May 2022. Results: Processors are under 45 years old, the majority is 75.9%, and 80.4% have an education level from illiterate to secondary school. The percentage of processors who meet the criteria of correct knowledge of food safety is 58.9 %, in which the rate of processors with knowledge of hygiene of tools reached the highest 83.0% and the rate of processors with knowledge of food poisoning reached the lowest 55.9%. There are 66.3% of processors achieved good food safety practices, 60.7% of processors were qualified to participate in food processing, in which 75.9% had a certificate of food safety education and 70.4% had a certificate check up health. Conclusion: The rate of street food processors achieving the criteria for correct knowledge and good practices on food safety is still low, therefore it is necessary to promote supervision and communication of food safety knowledge, especially food poisoning, in order to contribute to limiting the risk of food poisoning as well as food-borne diseases to ensure food safety for themselves and consumers.